2015
DOI: 10.1177/1359105315610811
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of psychological resilience and depression among left-behind children in China

Abstract: This prospective study examined the longitudinal effects of psychological resilience on depression in a Chinese sample of left-behind children. A total of 386 left-behind children completed both a baseline and a 1-year follow-up survey. The prevalence of depression at the baseline and 1-year follow-up was 12.7 and 8.5 per cent, respectively. Multivariate analysis revealed that older age and baseline depressive symptoms were positively associated with follow-up depression, while psychological resilience and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…First, the negative association between family resources and mental health addressed the seemingly inconsistent findings on the impact of parental migration on LBC's mental health. On the one hand, numerous studies have documented that LBC tend to experience symptoms of depression (J. Guo et al, ; Tomsa & Jenaro, ; Y. L. Wu et al, ), social anxiety (Dai & Chu, ; Man et al, ; Shi, Bai, Shen, Kenny, & Rozelle, ; Zhang & Xu, ), and other distress‐related symptoms (Ling et al, ; Su et al, ; Wickramage et al, ; C. Zhao et al, ). On the other hand, several studies indicate that LBC are less likely to experience poor mental health outcomes (Asis, ; Asis & Ruiz‐Marave, ; X. Guo et al, ) and that they tend to fare comparably with or better than non‐LBC (Asis, ; Graham & Jordan, ; Parreñas, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the negative association between family resources and mental health addressed the seemingly inconsistent findings on the impact of parental migration on LBC's mental health. On the one hand, numerous studies have documented that LBC tend to experience symptoms of depression (J. Guo et al, ; Tomsa & Jenaro, ; Y. L. Wu et al, ), social anxiety (Dai & Chu, ; Man et al, ; Shi, Bai, Shen, Kenny, & Rozelle, ; Zhang & Xu, ), and other distress‐related symptoms (Ling et al, ; Su et al, ; Wickramage et al, ; C. Zhao et al, ). On the other hand, several studies indicate that LBC are less likely to experience poor mental health outcomes (Asis, ; Asis & Ruiz‐Marave, ; X. Guo et al, ) and that they tend to fare comparably with or better than non‐LBC (Asis, ; Graham & Jordan, ; Parreñas, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the huge number of labor migrants has raised concerns regarding its social cost to families (Asis, ; Garabiles, Ofreneo, & Hall, ), and particularly to left‐behind children (LBC). A number of studies has shown that children who are left behind by their parents have poor mental health (Hu, Lu, & Huang, ; Ling, Fu, & Zhang, ; Mazzucato et al, 2015; Wen & Lin, ; Wickramage et al, ; C. Zhao, Wang, Li, Zhou, & Hesketh, ) and are likely to be at higher risk of experiencing symptoms of depression (J. Guo et al, ; He et al, ; Tomsa & Jenaro, ; L. Wang et al, ; Y. L. Wu et al, ), anxiety (Dai & Chu, ; Man, Mengmeng, Lezhi, Ting, & Jingping, ; Tomsa & Jenaro, ; Zhang & Xu, ), and social anxiety (Zhang & Xu, ). LBC have also been known to manifest low quality of life (Jia & Tian, ), low life satisfaction and happiness (F. Fan, Su, Gill, & Birmaher, ; Gao et al, ), difficulty in social adjustment (Jia & Tian, ), low self‐concept (X. Wang et al, ), and poor academic performance (Amuedo‐Dorantes & Pozo, ; Asis & Ruiz‐Marave, ).…”
Section: Mental Health Of Children: the Role Of Family As A Resourcementioning
confidence: 99%
“…But numerous studies have found higher prevalence of psychological [4] and behavioural problems [5, 6] in LBC than in NLBC in all age groups [4, 7, 8]. For example, LBC at older age were more likely to suffer from negative emotional experiences like depression [9], anxiety [7], loneliness [10] and neglect [11, 12], and have more conduct problems, including smoking [13] and alcohol consumption [14]. Besides, increasing number of left-behind adolescents were also reportedly sensitive, hostile and paranoid in their interpersonal relationship [15].…”
Section: Introductionmentioning
confidence: 99%
“…Wu and other researchers studied the left-behind children's resilience and depression in 2015 [6]. Zhang researched on the mental health status of left-behind children from the perspectives of isolation, lack of love, selfishness, rebellious attitude and weak rational consciousness in 2016 [7].…”
Section: Literature Reviewmentioning
confidence: 99%